Pengaruh Persepsi Harga, Iklan dan Kualitas Produk Terhadap Loyalitas Pelanggan Frestea di Wilayah Bandung Raya - Firjatulloh, Faisa Saskara; Hariyadi Triwahyu Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study seeks to analyze the impact of pricing perception, advertising, and product quality on customer loyalty to Frestea in the Greater Bandung region. This study is grounded in evidence of a decrease in consumer loyalty, as indicated by Top Brand Index data and Google Trends. This research utilizes a quantitative methodology through a survey administered to 100 participants who had ingested Frestea within the last three months. Data analysis was performed utilizing multiple linear regression with the aid of SPSS software version 25. The study's findings demonstrate that pricing perception, advertising, and product quality exert a favorable and considerable impact on consumer loyalty, both individually and collectively. Consequently, all presented theories may be accepted. These findings underscore the necessity of executing marketing strategies that fit with price rules, augmenting advertising efficacy, and preserving product quality to sustain and enhance consumer loyalty. This study aims to provide a reference for beverage industry stakeholders in formulating marketing strategies that correspond with customer preferences. Keywords: Price Perception, Advertising, Product Quality, Customer Loyalty, Frestea